Effects of positive end-expiratory pressure on intraoperative core temperature in patients undergoing posterior spine surgery: prospective randomised trial. Issue 3 (March 2018) - Seo, Hyungseok; Do Son, Je; Lee, Hyung-Chul; Oh, Hyung-Min; Jung, Chul-Woo; Park, Hee-Pyoung
Objective: Positive end-expiratory pressure (PEEP) causes carotid baroreceptor unloading, which leads to thermoregulatory peripheral vasoconstriction. However, the effects of PEEP on intraoperative thermoregulation in the prone position remain unknown. Methods: Thirty-seven patients undergoing spine surgery in the prone position were assigned at random to receive either 10 cmH2 O PEEP (Group P) or no PEEP (Group Z). The primary endpoint was core temperature 180 minutes after intubation. Secondary endpoints were delta core temperature (difference in core temperature between 180 minutes and immediately after tracheal intubation), incidence of intraoperative hypothermia (core temperature of <36°C), and peripheral vasoconstriction-related data. Results: The median [interquartile range] core temperature 180 minutes after intubation was 36.1°C [35.9°C–36.2°C] and 36.0°C [35.9°C–36.4°C] in Groups Z and P, respectively. The delta core temperature and incidences of intraoperative hypothermia and peripheral vasoconstriction were not significantly different between the two groups. The peripheral vasoconstriction threshold (36.2°C±0.5°C vs. 36.7°C±0.6°C) was lower and the onset of peripheral vasoconstriction (66 [60–129] vs. 38 [28–70] minutes) was slower in Group Z than in Group P. Conclusions: Intraoperative PEEP did not reduce the core temperature decrease in the prone position, although it resulted in an earlier onset and higher threshold of peripheral vasoconstriction.